2018
DOI: 10.1002/berj.3321
|View full text |Cite|
|
Sign up to set email alerts
|

The symbolic violence of setting: A Bourdieusian analysis of mixed methods data on secondary students’ views about setting

Abstract: 'Setting' is a widespread practice in the UK, despite little evidence of its efficacy and substantial evidence of its detrimental impact on those allocated to the lowest sets. Taking a Bourdieusian approach, we propose that setting can be understood as a practice through which the social and cultural reproduction of dominant power relations is enacted within schools. Drawing on survey data from 12,178 Year 7 (age 11/12) students and discussion groups and individual interviews with 33 students, conducted as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
(27 reference statements)
0
31
0
Order By: Relevance
“…Almost all study schools reported placing students in attainment groups strictly based on their prior attainment. Schools in the intervention group perhaps expectedly were more vocal about 'setting on ability rather than behaviour' (Richard, English teacher, School Q) although it should be noted that prior research suggests that the intention of group placement being based on prior attainment is not always realised, with social class for example being a significant predictor of group placement (Archer et al, 2018;Dunne et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all study schools reported placing students in attainment groups strictly based on their prior attainment. Schools in the intervention group perhaps expectedly were more vocal about 'setting on ability rather than behaviour' (Richard, English teacher, School Q) although it should be noted that prior research suggests that the intention of group placement being based on prior attainment is not always realised, with social class for example being a significant predictor of group placement (Archer et al, 2018;Dunne et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…(Max, mathematics teacher, School S) Max suggests that the current grouping practices in his school are not making the most of it as group placement decisions are infused with judgements about student behaviour. His frustration illustrates how a student's placement in the lowest attainment group results in misrecognition whereby his/her placement in the attainment grouping hierarchy can be interpreted by teachers as reflecting the student's innate 'ability' (Archer et al, 2018). There are also echoes of what Hamilton and O'Hara (2011) have insightfully referred to as the 'tyranny' of attainment grouping to highlight the power of attainment grouping as a school organising principle in an education system characterised by high-stakes testing.…”
Section: Context For Teaching and Learning In The Lower Attainment Grmentioning
confidence: 99%
“…; Francis et al ., ). The over‐allocation of black and working‐class students in lower sets in secondary schools has been described as a form of ‘symbolic violence’ (Archer et al ., ).…”
Section: Research On Grouping Practicesmentioning
confidence: 97%
“…Given the wider range of research on the reproduction of social inequalities through grouping (Gillborn & Youdell, ; Archer et al ., ), I would argue that systems of triage for the PSC may also reinforce disparities, by ‘leaving behind’ some children during this particular period. This may well operate alongside the systems of interventions already discussed, which involve withdrawing groups of children who are labelled ‘pupil premium’ or have English as an additional language.…”
Section: Educational Triage For the Phonics Screening Checkmentioning
confidence: 99%
“…In school (or university or workplace), taken-for-granted assumptions about fairness and merit underpin all that we do; and the illusio, further, is ‘a tacit recognition of the value of the stakes of the game and as practical mastery of its rules’ (Bourdieu and Wacquant, 1992: 117). Participants in the education ‘game’ must imagine rules applying equally to all players, as illustrated by two recent accounts (Archer et al., 2018; Griffiths, 2018) of the experiences children in year 7 (the first year of secondary school in England) have of setting: first, there is a relationship between class background and setting and, second, attitudes to setting as fundamentally fair and reasonable, accepted as such even by the ‘losers’, make up a key feature of the idea of meritocracy in schooling.…”
Section: Cultural Capital: a Research Traditionmentioning
confidence: 99%